The World Federation of Societies of Biological Psychiatry (WFSBP) Guidelines for the Biological Treatment of Bipolar Disorders: Acute and long-term treatment of mixed states in bipolar disorder - Grunze, H; Vieta, E; Goodwin, G; Bowden, C; Licht, R; Azorin, J; Yatham, L; Mosolov, S; Möller, H; Kasper, S (Taylor and Francis, 2017)
Objectives: Although clinically highly relevant, the recognition and treatment of bipolar mixed states has played only an underpart in recent guidelines. This WFSBP guideline has been developed to supply a systematic overview of all scientific evidence pertaining to the acute and long-term treatment of bipolar mixed states in adults. Methods: Material used for these guidelines is based on a systematic literature search using various data bases. Their scientific rigour was categorised into six levels of evidence (A–F), and different grades of recommendation to ensure practicability were assigned. We examined data pertaining to the acute treatment of manic and depressive symptoms in bipolar mixed patients, as well as data pertaining to the prevention of mixed recurrences after an index episode of any type, or recurrence of any type after a mixed index episode. Results: Manic symptoms in bipolar mixed states appeared responsive to treatment with several atypical antipsychotics, the best evidence resting with olanzapine. For depressive symptoms, addition of ziprasidone to treatment as usual may be beneficial; however, the evidence base is much more limited than for the treatment of manic symptoms. Besides olanzapine and quetiapine, valproate and lithium should also be considered for recurrence prevention. Limitations: The concept of mixed states changed over time, and recently became much more comprehensive with the release of DSM-5. As a consequence, studies in bipolar mixed patients targeted slightly different bipolar subpopulations. In addition, trial designs in acute and maintenance treatment also advanced in recent years in response to regulatory demands. Conclusions: Current treatment recommendations are still based on limited evidence, and there is a clear demand for confirmative studies adopting the DSM-5 specifier with mixed features concept.